The safety and efficacy of sonidegib for the treatment of locally advanced basal cell carcinoma. Issue 10 (2nd October 2016) - Collier, Nicholas J.; Ali, Faisal R.; Lear, John T.
ABSTRACT: Introduction: Basal cell carcinomas (BCCs) are the commonest malignancy in the Western world. Locally advanced BCCs (laBCCs) represent tumours that have developed in difficult-to-treat facial sites, aggressively recurrent tumours, large neglected tumours and those in which current treatment options are excluded by clinical or patient-driven criteria. It is estimated laBCCs represent 1% of BCCs. Areas covered: Sonidegib is an oral hedgehog pathway inhibitor with a novel structure. It has recently been licensed for the treatment of laBCC. This article provides a comprehensive review of the literature regarding sonidegib, detailing the pharmacology of the compound, clinical trial data, competitor compounds and a future perspective. Expert commentary: Sonidegib is a novel smoothened (SMO) inhibitor with comparable efficacy to vismodegib, with patient response rates of 44% (sonidegib) and 43% (vismodegib). The adverse effect profile of these two treatments is similar with the main effects being considered to be class effects of SMO inhibitors.